2022
DOI: 10.1111/1440-1703.12321
|View full text |Cite
|
Sign up to set email alerts
|

Preface: Functional biogeography in Japanese cedar

Abstract: The study of phenotypic and genotypic variation within species represents one of the main aspects of functional biogeography. This preface presents the geographic and historical background of genetic differentiation, its role as a foundation species, and the effects of variation in functional traits on ecosystem function based on the evolutionary ecology of Japanese cedar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…As C. japonica is one of the most widely distributed foundation species across the Japanese Archipelago, quantifying its intraspeci c variation in functional traits will help us understand how tree species moderate their physiological functions under changing environments in terms of functional ecology and evolutionary biology (Hiura 2023). This study is a few that assessed intraspeci c variations in ne root morphological traits caused only by different genotypic backgrounds using three provenance types of C. japonica trees planted in a common garden and suggested that intragenerational tree acclimation to the growing environment, that includes soil chemical alteration by plant-soil interactions (Ohta et al 2019), is possibly affected by genotypic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As C. japonica is one of the most widely distributed foundation species across the Japanese Archipelago, quantifying its intraspeci c variation in functional traits will help us understand how tree species moderate their physiological functions under changing environments in terms of functional ecology and evolutionary biology (Hiura 2023). This study is a few that assessed intraspeci c variations in ne root morphological traits caused only by different genotypic backgrounds using three provenance types of C. japonica trees planted in a common garden and suggested that intragenerational tree acclimation to the growing environment, that includes soil chemical alteration by plant-soil interactions (Ohta et al 2019), is possibly affected by genotypic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic variations of aboveground parts within a single species have been recognized in foundation species distributed across broad regions: for example, Japanese beech (Fagus crenata) and cedar (Cryptomeria japonicaD. Don) in the Japanese Archipelago (e.g., Hiura 1998 (Hiura 2023). However, genotypic variations in the ne root morphological traits of a single species remain unclear because it is di cult to separate the genotypic variations from trait variations owing to the growing environments.…”
Section: Introductionmentioning
confidence: 99%
“…Some tree species have a greater potential to absorb more nutrients and water in bedrock due to adaptation to the environment in which the tree species evolves (Dijkstra & Smits, 2002; Hiura, 2023; McCormick et al, 2021). Ohta et al (2019) showed that C. japonica has evolved root systems that are adapted to the environment of each provenance to increase nutrient absorption efficiency, and the ability to absorb nutrients from bedrock varies among the geographical populations.…”
Section: Discussionmentioning
confidence: 99%
“…How to cite this article: Ohta, T., & Hiura, T. (2023). The effects of functional differences in cultivar of Cryptomeria japonica on nutrient dynamics and soil invertebrates in a common garden.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Last year, three Special Features were published—“Functional biogeography: Lessons from the geographic variations in the most dominant tree species in Japan” in Issue 1; “Listen to the voices of local beech forests: An ecological and evolutionary conception of beech under phylogenetic and environmental constraints” in Issue 2; and “Blue carbon dynamics in coastal habitats: Their role in climate change mitigation and ecosystem function” in Issue 4 (see Hiura, 2023; Kitamura et al, 2023; Sharma et al, 2022 for prefaces, respectively). Your proposals for future Special Features are welcome and should be submitted to ecores@esj.ne.jp.…”
mentioning
confidence: 99%